The Effects of Social Media Tools Towards Online Retail Businesses in the Consumer Electronics Industry - Pre, Dave Matthew V; Tolentino, Julio Miguel C; Varuqez, Karlo Alexis B; Etrata, Antonio E. (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2022)
Businesses nowadays have been adapting to technological advancements since the 21st century to promote their products. The majo]rity of the global population has been exposed to the digital world, and retail businesses have engaged themselves in the online environment. Social media tools have become a significant factor in advertising products and have taken big steps to create innovations in their platforms. Using social media has given online businesses options on managing their performance towards their brand and how to interact with consumers. These digital enhancements toward flourishing online retail businesses have boosted the consumer electronics industry. The study's objective was to provide extensive knowledge of how the different social media platforms and tools significantly affected the performance of online retail businesses belonging to the consumer electronics industry. A quantitative research approach was utilized in this study. The researchers conducted online survey questionnaires and were distributed to 185 respondents. Lastly, the study aims to benefit retail businesses, consumers, and future researchers, who engage in online businesses and how they can stand out from prospective competitors.